First observation of the flowers of Sloanea dussii (Eleocarpaceae), a tree endemic to Martinique (Lesser Antilles): ecological, morphological, and taxonomical insights - Ferlay, Benjamin; Thésée, Alexandre (Phytotaxa, 2025)
Sloanea dussii is a species endemic to Martinique, Lesser Antilles. It was known only from very sporadic collections but inflorescences and flowers remained unknown. This paper includes a description, photographs, geographic distribution, and conservation assessment for the species. Taxonomic and nomenclatural considerations are also provided.